Cynicism, Pessimism, and Homophobia as Predictors of Negative Attitudes Towards People with HIV/AIDS - Nikolić, Miljana B.; Milićević, Nebojša M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The aim of the research was to examine whether it is possible to predict negative attitudes towards people with HIV/AIDS with the help of cynicism, pessimism, and homophobia. The sample was convenient and consisted of 100 respondents (M = 20, F = 80), average age 22.63 (SD = 5.04). The following instruments were used for the operationalization of the mentioned constructs: Scale of Pessimism, Scale of Cynicism, and Test of Homophobia (H25). To measure negative attitudes towards people living with HIV/AIDS, we used a subscale of the test which operationalizes the tendency to stigmatize and discriminate against people living with HIV/AIDS. Hierarchical linear regression was used to process the results. Predictors were pessimism, cynicism, and homophobia, while the criteria were negative attitudes towards people with HIV/AIDS. The results show that the first two models were not statistically significant, while the last model, after adding a variable that measures homophobia, becomes significant. The model composed of cynicism, pessimism, and homophobia explains 34% of the total variance (p = .00). Homophobia makes a significant contribution to the prediction, which is also a statistically significant predictor of negative attitudes towards people with HIV/AIDS (β = .54, t = 6.43, p = .00). Pessimism was also a statistically significant individual predictor (β = 20, t = 2.00, p = .05). It can be concluded that higher levels of pessimism and more pronounced homophobia significantly predict negative attitudes towards people with HIV/AIDS.